2021
DOI: 10.3390/nu13041074
|View full text |Cite
|
Sign up to set email alerts
|

Importance of EPA and DHA Blood Levels in Brain Structure and Function

Abstract: Brain structure and function depend on a constant and sufficient supply with eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) by blood. Blood levels of EPA and DHA reflect dietary intake and other variables and are preferably assessed as percentage in erythrocytes with a well-documented and standardized analytical method (HS-Omega-3 Index®). Every human being has an Omega-3 Index between 2 and 20%, with an optimum of 8–11%. Compared to an optimal Omega-3 Index, a lower Omega-3 Index was associated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
57
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(60 citation statements)
references
References 184 publications
0
57
1
2
Order By: Relevance
“…A number of analyses have reported positive associations between DHA or EPA + DHA status in blood lipids fractions and cognitive outcomes (129)(130)(131) . In the Framingham Cohort, high v. low (Q4 v. Q1) phosphatidylcholine-DHA was associated with a 47 % reduction in all cause dementia (129) .…”
Section: Fish and Dha Intake And Status And Cognition: Prospective Co...mentioning
confidence: 99%
“…A number of analyses have reported positive associations between DHA or EPA + DHA status in blood lipids fractions and cognitive outcomes (129)(130)(131) . In the Framingham Cohort, high v. low (Q4 v. Q1) phosphatidylcholine-DHA was associated with a 47 % reduction in all cause dementia (129) .…”
Section: Fish and Dha Intake And Status And Cognition: Prospective Co...mentioning
confidence: 99%
“…Diets rich in linoleic acid and other omega-6 fatty acids inhibit the metabolic formation of omega-3 polyunsaturated fatty acids, which can lead to a deficit of eicosapentaenoic acid (EPA) 23 and is associated with reduced brain volume, impaired cognition, and accelerated progression to dementia. 24 Our study showed that increased levels of linoleic acid were associated with higher WMH volume.…”
Section: Discussionmentioning
confidence: 48%
“…There is an increasing body of evidence confirming a relationship between low omega-3 polyunsaturated fatty acids status and depression [ 186 ]. Docosahexaenoic acid (DHA) is the most prevalent omega-3 fatty acid in brain tissue and is critical for brain development and health [ 187 ]. In an animal study, compared with the administration of α-linolenic (ALA) alone (a precursor to DHA), its delivery in combination with curcumin enhanced the synthesis of DHA, elevated levels of enzymes involved in the synthesis of DHA such as fatty acid desaturase 2 and elongase 2, and increased DHA concentrations in both liver and brain tissue.…”
Section: Curcumin’s Potential Antidepressant Mechanisms Of Actionmentioning
confidence: 99%